Comparative Study Of Students‘ Approaches And Strategies To Learning: Implications For Counselling - Tijani, Fatimah Y.; Abimbola, O. Grace; Jane, Namusoke; Adeyemi, T.S; Egbekunle, Emmanuel A; Kehinde, E.O (European Scientific Journal, ESJ, 2016)
The researchers compared students’ approaches and strategies to learning in two African countries viz.; Nigeria and Uganda. Using a descriptive survey, fifty students, who were enrolled in the year 2012/2013 in guidance and counselling and computer science respectively, were sampled from the population. The students offered an ICT course separately in 200 level in the different institutions. The instrument used was the Approaches to study skills inventory (ASSIST) and the three hypotheses were postulated and tested. The results of the t-test analysis show that the null hypothesis was not statistically significant when using the strategic approach (t = 1.037, 1.056); p > .05 and the deep approach to learning of students in Nigeria and Uganda (t = -0.278, -0.279); p > .05. The second hypotheses revealed a no statistically significant difference in the Nigerian and Ugandan preferences for different types of courses in teaching and learning while the third hypothesis shows a significant correlation between a deep approach to learning and learning that supports understanding (r=.407; p <.001). It is recommended that lecturers need to accommodate their students’ individual differences in the teaching and learning process considering that most of the classes in higher institutions of learning are large for the prevalent part. Additionally, discussions on possible implications for counselling are discussed in the paper.